Copper(I)‐Catalyzed Stereoselective Synthesis of (E)‐α‐Alkynyl‐α, β‐unsaturated Esters from a Terminal Alkyne, Diazoesters and Aldehydes. Issue 15 (1st August 2016) - Wu, Chenggui; Liu, Zhenxing; Zhang, Zhikun; Ye, Fei; Deng, Guisheng; Zhang, Yan; Wang, Jianbo
Abstract: A new synthetic method for α‐alkynyl‐α, β‐unsaturated esters is presented herein. The method is based on a copper(I)‐catalyzed three‐component reaction of a terminal alkyne, diazoesters and aldehydes. The reaction is featured by mild conditions, high yields and excellent stereoselectivity. Cu(I) carbene migratory insertion is proposed as the key step in the transformation. Abstract :